THE POSITIVE ANALYSIS ABOUT THE CONDITION OF CHINESE TECHNOLOGY GAIN FDI - Hongyi BI; Sofia Elena COLESCA (Management & Marketing)
The technical level in 21st century will directly decide the internationalcompetition ability of a country and become the core factor which theinternational competition will subdue. Using the reverse effect of shift oftechnology in foreign investment, a company gains advanced technologythrough foreign investment and shift it to the investment country, whichmovement we call it technical gain FDI. Various countries in the worldespecially the developing countries, such as China, its research level and theenvironment can’t adapt the demand of economic globalization. So it is arealistic choice to the developing countries to develop technology gaininvestment and combine with the other foreign investment to gain theadvanced technology.